AZFa Y gene, DDX3Y, evolved novel testis transcript variants in primates with proximal 3´UTR polyadenylation for germ cell specific translation - Vogt, Peter H.; Rauschendorf, Marc-Alexander; Zimmer, Jana; Drummer, C.; Behr, R. (Scientific reports, 2022)
Translational control is a major level of gene expression regulation in the male germ line. DDX3Y located in the AZFa region of the human Y chromosome encodes a conserved RNA helicase important for translational control at the G1-S phase of the cell cycle. In human, DDX3Y protein is expressed only in premeiotic male germ cells. In primates, DDX3Y evolved a second promoter producing novel testis-specific transcripts. Here, we show primate species-specific use of alternative polyadenylation (APA) sites for these testis-specific DDX3Y transcript variants. They have evolved subsequently in the 3´UTRs of the primates´ DDX3Y transcripts. Whereas a distal APA site (PAS4) is still used for polyadenylation of most DDX3Y testis transcripts in Callithrix jacchus; two proximal APAs (PAS1; PAS2) are used predominantly in Macaca mulatta, in Pan trogloydates and in human. This shift corresponds with a significant increase of DDX3Y protein expression in the macaque testis tissue. In chimpanzee and human, shift to predominant use of the most proximal APA site (PAS1) is associated with translation of these DDX3Y transcripts in only premeiotic male germ cells. We therefore assume evolution of a positive selection process for functional DDX3Y testis transcripts in these primates which increase their stability and translation efficiency to promote its cell cycle balancing function in the human male germ line.
Gesehen am 30.06.2022